Biomechaniceskij analiz položenija udarnogo zvena pri napadajušcem udare v volejbole - Polezhaeva, O. N.; Laptev, A. V.; Volokhova, S. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article identifies the main ways of positioning the strike link in the final phase of the swing during an attack hit in volleyball. Using a biomechanical video analysis, the sequence of the swing phase is analyzed and described. Biomechanical analysis was performed using Kinovea and SkilSpektor software. The identified main methods of the shock phase allow you to make timely changes to the training process and adjust the technique based on the individual anatomical and biomechanical characteristics of the players.